Correlation of Spleen Weight with Body Temperature and Cycle Threshold Value of Bali Cattle Given Jembrana Virus Inoculum - Yoga Cahya Mahardika; Pungky Slamet Wisnu Kusuma; Tatang Sopandi (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2026)
Beef demand in Indonesia continues to increase, particularly during religious holidays. Bali cattle, one of the main sources of beef, face a serious threat from Jembrana disease, a viral infection that compromises the immune system and causes significant economic losses. This study aimed to determine the correlation between spleen weight, body temperature, and cycle threshold (Ct) values in Bali cattle following Jembrana virus inoculation. A correlational method was applied to eight female Bali cattle injected with Jembrana virus inoculum. Physiological changes in body temperature were monitored, followed by necropsy to assess spleen weight. In addition, Real-Time Polymerase Chain Reaction (RT-PCR) was performed before and after inoculation to detect viral presence and determine Ct values. Data were analyzed using SPSS with Pearson correlation tests. The results revealed a very strong positive correlation between spleen weight and body temperature, while a very strong negative correlation was observed between spleen weight and Ct values. These findings indicate that Jembrana virus inoculation leads to increased body temperature and splenic enlargement in Bali cattle, accompanied by a decrease in Ct values, reflecting higher viral loads. Therefore, the administration of antipyretics, anti-inflammatory drugs, analgesics, vitamins, and antibiotics prior to vaccination is recommended to reduce the risk of hyperthermia, splenic swelling, decreased Ct values, and secondary infections.